2005
DOI: 10.1111/j.1460-2695.2005.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue as a process of cyclic brittle microfracture

Abstract: A B S T R A C T While fatigue crack growth in vacuum may occur by slip alone, environmental fatigue including crack growth in air is strongly influenced by crack-tip surface chemistry that adversely affects ductility. Cumulative diffusion, combined with adsorption and chemisorption in the loading half-cycle may promote instantaneous crack extension by brittle microfracture (BMF). Unlike slip, the BMF component will be sensitive to parameters that affect near-tip stresses, such as load history and constraint. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Either of these mechanisms could produce a path without a preferred low-index crystallographic plane, consistent with the results of the present study. Sunder speculates that near-threshold fatigue crack extension in Al alloys is dominated by brittle microfracture of an unspecified environmental surface reaction film, [81] paralleling this discussion. However, the environmental exposure conditions for the present research likely involve rapid surface reaction saturation and H-diffusion limitation, justifying the volumetric H-embrittlement perspective.…”
Section: Crack Tip Slip Based: Help and Aidementioning
confidence: 85%
“…Either of these mechanisms could produce a path without a preferred low-index crystallographic plane, consistent with the results of the present study. Sunder speculates that near-threshold fatigue crack extension in Al alloys is dominated by brittle microfracture of an unspecified environmental surface reaction film, [81] paralleling this discussion. However, the environmental exposure conditions for the present research likely involve rapid surface reaction saturation and H-diffusion limitation, justifying the volumetric H-embrittlement perspective.…”
Section: Crack Tip Slip Based: Help and Aidementioning
confidence: 85%
“…A programmed loading sequence was periodically interspersed to create microscopic marks on the fracture surface, as shown in Fig. 2 21,22,72–75 . Marker loads were applied with the baseline σ max , but R = 0.1 and f = 10 Hz.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This mechanism is consistent with recent focus on both DK and K MAX control of intrinsic fatigue crack-tip damage. [45,65] Preliminary TEM analysis of a thin foil, prepared from the environmental-fatigue crack wake by focused ionbeam machining, demonstrated that an approximately 200-nm-diameter dislocation-cell structure formed in naturally aged Al-Cu-Mg, presumably due to recovery of high strain from crack-tip deformation. The fatigue crack appeared to travel both along and through this dislocation structure.…”
Section: Environmental-fatigue Crack-tip Damage Mechanism Implicatmentioning
confidence: 99%
“…Moist-environment enhancement of fatigue-crack propagation in the low growth-rate regime is reasonably attributed to hydrogen embrittlement in precipitationhardened aluminum alloys, [1][2][3]28,29,45] rather than a per cycle geometrically based plasticity mechanism. [25][26][27]46,47] (For the present work, cyclic plastic zone size is on the order of 3 lm, environment enhanced da/dN is on the order of 0.003 lm/cycle (Figure 1), and fatigue-crack advance is likely discontinuous over a distance of a fraction of a micrometer and requiring several hundred load cycles.)…”
Section: Environmental-fatigue Crack-tip Damage Mechanism Implicatmentioning
confidence: 99%